GPU-Accelerated and CPU SIMD Optimized Monte Carlo Simulation of φ4 Model - Białas, Piotr; Kowal, Jakub; Strzelecki, Adam (Computing and Informatics, 2015)
In this contribution we describe an efficient GPU implementation of the Monte-Carlo simulation of the Ginzburg-Landau model. We achieve the performance close to 50 % of the peak performance of the used GPU. We compare this performance with a parallelized and vectorized CPU code and discuss the observed differences.